TRANSLATION REVIEW ON THE TERM AANSLAG TO MAKAR IN THE CRIMINAL CODE OF INDONESIA - Rian, Frans (Journal of Language, Literature and Teaching, 2023)
Dutch-Indonesian legal translation is under studied. The absence of equivalent terms in different languages requires constant comparison between SL (source language) and TL (target language) legal systems. Legal translators face numerous challenges as a result of the asymmetry between Dutch and Indonesian, whether those challenges are linguistic or cultural. Dutch and Indonesian terms are elements of linguistic difference and there is no one-to-one correspondence in Indonesian legal discourse. These require more effort from the translator. As cultural mediators, Indonesian legal translators may strive to understand Dutch terms conceptually rather than translate them literally. As in this study, the discussion of lexical translation between Dutch and Indonesian between makar and aanslag is the main goal. Because the term Makar has multiple meanings and is used to translate the word aanslag in Indonesia's criminal code, there is currently much debate over its use. This ambiguity prevents legal certainty from being guaranteed. The current situation with Indonesia's criminal code is that it does not define or set limitations on Macar acts, making possible uncertainties. The paper comes to the conclusion that translating the lexical terms mentioned above calls for knowledge of the linguistic and legal systems of languages, professional training, and up-to-date electronic dictionaries. This paper uses Library Research Method adapted from Thomas Mann. Data collections are collected from Published Sources, Online Databases, Government and Institutional Records, Publicly Available Data, and Past Research Studies.